Work Flexibility and Income as Determinants of Performance of Online Motorcycle Taxi Drivers in Medan City - Tambunan, Debora; Sibarani, Hendra Jonathan; Pakpahan, Dewi Rafiah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyse the effect of work flexibility and income on the performance of online motorcycle taxi drivers in Medan City. Based on the results of data analysis, it was found that work flexibility has a significant influence on employee performance, with a t-count value of 2.789 greater than the t-table of 1.984 and a significance value of 0.000 which is smaller than 0.05. Income or salary also shows a positive and significant influence on driver performance, with a t-count value of 3.768 greater than the t-table 1.984 and a significance value of 0.012 which is smaller than 0.05. In addition, simultaneous hypothesis testing shows that work flexibility and income together have a significant effect on employee performance, with an F-count value of 3.675 which is greater than the F-table of 3.090 and a significance value of 0.000 which is smaller than 0.05. These results indicate that work flexibility and income have a significant influence on improving the performance of online motorcycle taxi drivers in Medan City.